Species Traits and Geomorphic Setting as Drivers of Global Soil Carbon Stocks in Seagrass Meadows. Issue 10 (17th October 2022) - Kennedy, H.; Pagès, J. F.; Lagomasino, D.; Arias‐Ortiz, A.; Colarusso, P.; Fourqurean, J. W.; Githaiga, M. N.; Howard, J. L.; Krause‐Jensen, D.; Kuwae, T.; Lavery, P. S.; Macreadie, P. I.; et al.
Abstract: Our knowledge of the factors that can influence the stock of organic carbon (OC) that is stored in the soil of seagrass meadows is evolving, and several causal effects have been used to explain the variation of stocks observed at local to national scales. To gain a global‐scale appreciation of the drivers that cause variation in soil OC stocks, we compiled data on published species‐specific traits and OC stocks from monospecific and mixed meadows at multiple geomorphological settings. Species identity was recognized as an influential driver of soil OC stocks, despite their large intraspecific variation. The most important seagrass species traits associated with OC stocks were the number of leaves per seagrass shoot, belowground biomass, leaf lifespan, aboveground biomass, leaf lignin, leaf breaking force and leaf OC plus the coastal geomorphology of the area, particularly for lagoon environments. A revised estimate of the global average soil OC stock to 20 cm depth of 15.4 Mg C ha −1 is lower than previously reported. The largest stocks were still recorded in Mediterranean seagrass meadows. Our results specifically identify Posidonia oceanica from the Mediterranean and, more generally, large and persistent species as key in providing climate regulation services, and as priority species for conservation for this specific ecosystem service. Key Points: To understand global drivers of seagrass carbon stocks, we compiled data on species traits and stocks at multiple geomorphological settings Globally, we identify large and long‐lived seagrass species in lagoon environments as key in providing climate regulation services The Mediterranean is a hotspot of seagrass carbon sequestration, given the distinct capacity of Posidonia oceanica to support large stocks